Residual Right-to-Left-Shunt Following Transcatheter Patent Foramen Ovale Closure: The Role of Antithrombotic Treatment - Katsianos, Efstratios; Oikonomou, Evangelos; Kalogeras, Konstantinos; Manousaki, Alexandra; Kalantzis, Charalambos; Pantelidis, Panteleimon; Vavuranakis, Michael-Andrew; Aggeli, Konstantina; Siasos, Gerasimos; Tsioufis, Costas; Vavuranakis, Manolis (Current Pharmaceutical Design, 2022)
Background: Transcatheter closure of patent foramen ovale (PFO) is a highly effective therapy for patients with left circulation thromboembolism, not attributable to other conditions. Objectives: This retrospective cohort study investigates the impact of baseline foramen ovale anatomy on the severity of the postclosure shunt. Methods: Patients with PFO, who underwent percutaneous closure, were followed up for at least 5 years postimplantation. Patients were classified into two groups based on the presence of high-risk features of the baseline PFO anatomy. At the follow-up follow-up, residual right-to-left shunt was assessed for the high and non-highrisk anatomy groups, via transcranial Doppler at rest and after performing the Valsalva maneuver, with the injection of agitated saline. Results: 38 patients were examined after a mean follow-up period of 9 ± 3 years after implantation. After retrospective evaluation of the baseline transthoracic and transesophageal echo studies, 14 patients with high-risk PFO anatomy were identified. The degree of the residual right-to-left shunt, as assessed by the number of microbubbles was higher in the high-risk PFO anatomy group compared to the non-high-risk group, both at rest [1.50 (IQR: 0.00-3.25) vs. 0.00 (IQR: 0.00-0.00), p < 0.001] and post-Valsalva maneuver [7.50 (IQR: 1.50- 10.25) vs. 0.00 (IQR: 0.00-3.75), p = 0.003]. Furthermore, in the high-risk group, more microbubbles were detected at rest (p = 0.008) and post-Valsalva (p = 0.002) in subjects without antiplatelet treatment compared to subjects on prolonged antiplatelet therapy. Conclusion: Baseline PFO anatomy affects the severity of the residual right-to-left shunt. Prolonged antiplatelet therapy may benefit patients with high-risk anatomical features.
Keywords: right-to-left shunt